(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The purpose of providing a framework for understanding development problems in a postcolonial environment, the purpose of this research is to investigate the ways in which postmodernism and postcolonialism interact with one another. The focus of the study is on the development of postcolonial feminist literary criticism, which involves analyzing global narratives through the lens of gender, racism, and social class. Through the perspective of the South, this research investigates feminist postcolonial critical views, bringing to light the ways in which intersectionality influences development discourse. The work investigates the ways in which the feminization of employment and resource allocation influences the multiplicative effects of gender discrimination, subjection of women, and women’s agency. Rather than the additive effects, the multiplicative effects are more prevalent. Furthermore, it underlines how important intersectional techniques are for appreciating these issues in the social and territorial South, as well as in the North as a whole, where problems of racial and social marginalization continue to exist as a result of migration, slavery, and other factors. In the last half of the paper, the author emphasizes the significance of intersectionality in feminist postcolonial literary criticism. This is done in order to present a full assessment of global narratives.